Analisis Besar Potongan Harga Discount Treatment Melalui Bauran Komunikasi Pemasaran di Klinik Kecantikan the Alfein - Alya Siti Dwi Julia; Agustini Agustini; Muhammad Lutfie (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
The beauty industry continues to grow rapidly throughout the world, triggering increasingly fierce competition among beauty clinics. Promotional strategies, especially offering treatment discounts, are key in maintaining and increasing market share. This research investigates the major price discount strategy through the marketing communications mix at The Alfein Beauty Clinic in Bogor City. Qualitative research methods were used through in-depth interviews and direct observation. The results show that the size of the price discount, the promotional period, and the type of product offered influence the success of the promotional strategy. Social, cultural, individual, and psychological factors also play a role in consumer purchasing behavior. In conclusion, a deep understanding of these dynamics is important in developing effective marketing strategies. The size of the discount, the promotional period, and the type of product must be considered carefully. Understanding social, cultural, individual, and psychological factors helps design responsive promotions. This research provides valuable insights for the beauty industry in facing competition and increasing consumer satisfaction.